Can media exposure improve stock price efficiency in China and why? - Jeong-Bon Kim; Zhongbo Yu; Hao Zhang (China Journal of Accounting Research, 2016)
The media in China has undergone extensive commercialization to become more market-driven over the last 35 years. Based on a sample of over two million newspaper articles, this study investigates whether the media in China has an incremental impact on stock price efficiency. We find that: as media coverage of a firm increases, (1) its stock price synchronicity decreases; (2) the probability of informed trading of its stock increases; and (3) the extent to which its stock price deviates from random walk decreases. Our inter-regional analysis over thirty-one provinces/regions within China reveals that the effects of the media on decreasing stock price synchronicity, increasing the probability of informed trading, and reducing stock price deviation from random walk are stronger in regions of weaker institutional development. Our findings suggest that a market-driven media can play the role of compensating for the underdeveloped governance institutions in transitional economies such as China.
Keywords: G14; G30; 650; Media exposure; Stock price efficiency; China